Pengoptimalan Ruang Cargo Kapal Kelas I Kenavigasian Tanpa Pillar dengan Pemodelan - susianto (Techno Bahari, 2021)
Deck Load Capacity is the ability of a deck to accommodate a number of heavy loads, expressed in tons / m², can be found in the ship's capacity plan where you can find out how much each deck is capable, calculate high the maximum arrangement of the load is so that it does not exceed the deck strength. Navigation is everything related to Sailing - Navigation Assistance Facilities, Sailing Telecommunications, hydrography and meteorology, channels and crossings, dredging and reclamation, guidance, handling of ship frames, salvage and underwater work for the benefit of shipping safety. The planning of deck load for Kapal Kelas 1 Kenavigasian must also pay attention to the workload of the deck consisting of pedestal cranes, buoys and armature buoy with a load of 5-10 tons. By doing calculations and modeling with MSC PATRAN and MSC NASTRAN. By modeling with software, you will get a profile that can withstand loads on the deck so that the cargo space does not need to be installed pillars. From this modeling, it is hoped that it can be used on all navigation ships with a maximum deck load of 10 tons on the next navigation ship.aplication all navigation ships with a maximum deck load of 10 tons on the next navigation ship.